Crustal Groundwater Volumes Greater Than Previously Thought. Issue 16 (17th August 2021) - Ferguson, Grant; McIntosh, Jennifer C.; Warr, Oliver; Sherwood Lollar, Barbara; Ballentine, Christopher J.; Famiglietti, James S.; Kim, Ji‐Hyun; Michalski, Joseph R.; Mustard, John F.; Tarnas, Jesse; McDonnell, Jeffrey J.
Abstract: Global groundwater volumes in the upper 2 km of the Earth's continental crust—critical for water security—are well estimated. Beyond these depths, a vast body of largely saline and non‐potable groundwater exists down to at least 10 km—a volume that has not yet been quantified reliably at the global scale. Here, we estimate the amount of groundwater present in the upper 10 km of the Earth's continental crust by examining the distribution of sedimentary and crystalline rocks with depth and applying porosity‐depth relationships. We demonstrate that groundwater in the 2–10 km zone (what we call "deep groundwater") has a volume comparable to that of groundwater in the upper 2 km of the Earth's crust. These new estimates make groundwater the largest continental reservoir of water, ahead of ice sheets, provide a basis to quantify geochemical cycles, and constrain the potential for large‐scale isolation of waste fluids. Plain Language Summary: Global groundwater volumes in the upper 2 km of the Earth's continental crust, which include important potable water supplies, are well estimated. At greater depths, a vast body of largely saline water exists down to at least 10 km and this volume that has not yet been quantified reliably at the global scale. Here, we estimate the amount of groundwater present in the upper 10 km of the Earth's continental crust. We demonstrate that groundwater between 2 and 10 km deep has a volume comparable to that of groundwater in the upper 2 km of the Earth's crust. These new estimates make groundwater the largest continental reservoir of water, ahead of ice sheets. This large volume of fluid, which is thought to be largely disconnected from the rest of the hydrologic cycle, is largely uncharacterized. Key Points: Groundwater is the largest continental store of water, liquid or otherwise The volume of deep saline groundwater is similar to shallow potable groundwater Deep groundwater systems remain largely unexplored